Studi Komunikasi Budaya Masyarakat Toraja di Jakarta (Upaya Masyarakat Toraja Mempertahankan Budaya Asli) - Irvan Andress Anthony; Suzy Azeharie (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
Toraja is an area that has many unique cultures. However, over time many native Toraja people left hometown, and went to wander outside Toraja, one of which was Jakarta. The research with the title